Smalltracer: Um verificador de tipos e condições para Smalltalk - Meira, Silvio R. L.; Lisboa, Paulo H. C. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1992)
This paper discusses the difficulty of today's object oriented languages and programming environments to keep together some benefits of the paradigm, such as fast prototyping and linguistic unity in a rider range of stages of the software life cycle. A type and condition environment, Smalltracer is proposed here as a possible solution for some of the problems that occur in Smalltalk and in the Smalltalk/V environment.